SIGNIFICANCE OF THE MEANING OF PERSONAL LIFE IN CRISIS CONDITIONS: POSSIBILITIES OF LOGOTHERAPY - Yalanska, Svitlana (European Science, 2023)
Today, in the conditions of the war in Ukraine, the importance of an individual’s understanding of his own meaning in life is quite clearly observed. What determines the actions and attitude towards the events experienced by Ukrainians. Therefore, the ans